Efectos de tabaquismo sobre los valores de Fibrinógeno y Lipoproteínas sanguíneas en varones de 30 a 50 años de edad, que habitan en el cantón Chilla - provincia de El Oro. - Ramón Orellana, Carlota I. (2008)
The tabaquismo is accepted as risk factor for the development he/she gives breathing cardiovascular diseases and neoclassical that are the main cause he/she gives death in the whole world. Inside the cardiovascular diseases for tobacco stands out the atherosclerosis, responsible for the reduction dives the arterial light due to the cellular proliferation in the arterial walls, accumulation gives lipids and finally, production gives badges ateromatosas.